Opening the Treasure Chest: The Current Status of Research on Brassica oleracea and B. rapa Vegetables From ex situ Germplasm Collections - Witzel, Katja; Kurina, Anastasia B.; Artemyeva, Anna M. (Frontiers in Plant Science, 2021)
Germplasm collections reflect the genetic variability in crops and their wild relatives. Hence, those genetic resources are tremendously valuable for breeders and researchers, especially in light of climatic change and stagnant crop production rates. In order to achieve improvements in crop production and end-use quality, favorable traits and donor alleles present in germplasm collections need to be identified and utilized. This review covers recent reports on the utilization of germplasm material to isolate genotypes of Brassica oleracea and B. rapa vegetables, focusing on high nutrient use efficiency, accumulation of biologically active metabolites, pest resistance and favorable phenotypic appearance. We discuss the current state of Brassica vegetable collections in genebanks and summarize studies directed to the molecular characterization of those collections.